Studi Kebijakan Penanggulangan Kejahatan Cyber Crime dan Pencemaran Nama Baik di Ruang Siber (Kasus Direktorat Kriminal Khusus Subdit V Cyber Crime Polda Sumatera Utara) - Henny April Yanti Bu’ulolo; Anggreini Atmei Lubis; Wenggedes French (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Criminal policy represents the rational strategy of society in addressing criminal activities. Criminal law policy is a subfield of criminal law science that focuses on crime prevention. In Indonesia, the government has enacted Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law) to regulate the use of information technology and social media, aiming to maintain justice, public order, and legal certainty. Defamation refers to actions that harm an individual's reputation through spoken or written words. Article 27 paragraph (3) of the ITE Law regulates defamation. This research explores both penal and non-penal policies in addressing defamation crimes in cyberspace. A normative juridical method is employed to analyze legal solutions to this issue. Primary, secondary, and tertiary data are combined to investigate this matter. A population and sample approach is utilized to answer the research questions. This study analyzes the effectiveness of criminal and non-criminal policies in dealing with online defamation, providing crucial insights for future regulatory enhancements.